Increasing concentrate feeding level in early lactation dairy cows fed cut herbage linearly decreased methane yield and intensity - Maria M. Della Rosa; Troy J. Bosher; M. Ajmal Khan; Edgar Sandoval; German Molano; Brenna Dobson-Hill; Federico N. Duranovich; Arjan Jonker (Animal Nutrition, 2025)
The use of supplementary feeds, including concentrates, on New Zealand dairy farms has increased in recent decades and this could have mitigated methane (CH4) emissions by decreasing the forage-to-concentrate ratio. The forage-to-concentrate ratio in the diet can be easily managed in cows that receive a total mixed ration, but under grazing conditions, the cows select their own diets by increasing or decreasing the herbage intake, likely depending on the amount of concentrates eaten. The feed selection will have a direct effect on the forage-to-concentrate ratio and the potential mitigation of CH4 emissions. The objective of the current study was to determine the effect of feeding increasing levels of concentrates in pasutre fed early lactation dairy cows on CH4 emissions. Thirty-two early lactation dairy cows fed fresh cut ryegrass-based herbage ad libitum were allocated to receive 0, 2, 4 and 6 kg dry matter of concentrates (n = 8 per treatment) per day in two equal meals during milking. The cows were on their respective full treatment diets for at least 14 days before CH4 measurements started. The CH4 emissions were measured in respiration chambers for 48 h. The CH4 yield (g/kg dry matter intake) and intensity (g/kg milk solids) decreased linearly by 0.76 and 5.3 units per kg of concentrate in the diet (P = 0.001 and P = 0.009), respectively, with increasing the concentrate level. The variations in CH4 emissions after each feeding increased quadratically and linearly (P = 0.023 and P = 0.038) after morning and afternoon feeding, respectively and the CH4 emissions reached the peak more rapidly after morning feeding (linear effect; P = 0.029) when the concentrate level increased. For short-chain fatty acids, the proportion of acetate decreased by 0.72 units (P = 0.003) while the proportion of propionate increased by 0.16 units (P = 0.006) per kg of concentrate in the diet. Feeding concentrates is a simple feeding strategy to mitigate CH4 emissions from dairy cows. CH4 yield decreased linearly by increasing the concentrate inclusion level of the diet.